Does craving for cocaine mediate cocaine use? Analysis of a randomized controlled pilot trial of memory-focused cognitive therapy. Issue 3 (3rd July 2019) - Goetz, Camille; Meynen, Tim; Mitcheson, Luke; Grey, Nick; Eastwood, Brian; Strang, John; Marsden, John
Cocaine use disorder (CUD) is a debilitating psychopathology, with no recommended medication therapy or specific psychological intervention. Memory-focused cognitive therapy (MFCT) is a novel psychotherapy for CUD, theorized to modify and reconsolidate cocaine craving-related memories for cognitive and behavioral control. A pilot randomized controlled trial indicated that this therapy is associated with reduced craving and cocaine use. With an 80% confidence interval (CI) set for null hypothesis testing, we conducted an exploratory causal mediation analysis with confounder adjustment to determine whether increased cocaine abstinence following MFCT is mediated by reduced craving experience and increased emotion regulation. Participant data on the Difficulties in Emotion Regulation Scale did not meet screening evaluation as a potential mediator. Cocaine craving (assessed by the frequency version of the Craving Experiences Questionnaire) was associated with a total treatment effect of MFCT on cocaine abstinence at follow-up (1.499; 80% CI 1.114 to 1.970; p = .012). A significant natural indirect effect indicated that reductions in cocaine use were strongly mediated by reduced frequency of craving experience (1.753; 80% CI: 1.334 to 2.936; p < .0001). This study provides exploratory evidence in support of the theoretical action for MFCT and underscores the importance of craving as a therapeutic target.